Dissecting CD8+ T cell pathology of severe SARS-CoV-2 infection by single-cell immunoprofiling - Schreibing, Felix; Hannani, Monica T.; Kim, Hyojin; Nagai, James S.; Ticconi, Fabio; Fewings, Eleanor; Bleckwehl, Tore; Begemann, Matthias; Torow, Natalia; Kuppe, Christoph; Kurth, Ingo; Kranz, Jennifer; et al. (Frontiers in immunology, 2022)
SARS-CoV-2 infection results in varying disease severity, ranging from asymptomatic infection to severe illness. A detailed understanding of the immune response to SARS-CoV-2 is critical to unravel the causative factors underlying differences in disease severity and to develop optimal vaccines against new SARS-CoV-2 variants.
Gesehen am 21.02.2023